Zooming to Class? Experimental Evidence on College Students' Online Learning during COVID-19 - Kofoed, Michael S.; Gebhart, Lucas; Gilmore, Dallas; Moschitto, Ryan (American Economic Review: Insights, 2024)
One persistent question in higher education is the efficacy of online education. In the fall of 2020, we randomized 551 West Point students in a required introductory economics course across 12 instructors to either an online or in-person class as a response to the COVID-19 pandemic. Final grades for online students dropped by 0.215 standard deviations, a result apparent in both assignments and exams and largest for academically at-risk students. A postcourse survey finds that online students struggled to concentrate in class and felt less connected to their instructors and peers. Our results show detrimental effects for online learning.
Keywords: Economic Education; Higher Education; Research Institutions; Teaching of Economics; Undergraduate; Health Behavior